2022
DOI: 10.1101/2022.09.15.508073
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A network of Notch-dependent and -independent her genes controls neural stem and progenitor cells in the zebrafish thalamic proliferation zone

Abstract: Neural proliferation zones mediate brain growth, and employ Delta/Notch signaling and HES/HER transcription factors to balance neural stem cell (NSC) maintenance and generation of progenitors and neurons. We investigated Notch-dependency and function of her genes in the thalamic proliferation zone of developing zebrafish larvae. Nine Notch-dependent genes, her2, her4.1-5, her12, her15.1-2, and two Notch-independent genes, her6, her9, are differentially expressed, and define distinct NSC and progenitor populati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
(121 reference statements)
2
2
0
Order By: Relevance
“…Its expression is enriched in boundary cells compared to rhombomere compartments at early stages, and it remains mainly in proliferating radial glial cells of lateral domains all along the AP axis at later stages. Our results support the developmental strategy othat different Hes/Her genes maintain distinct neural progenitor populations (Chapouton et al , 2006; Stigloher et al , 2008; Sigloch et al , 2023) establishing the neurogenic asynchrony in neural tissues. Hindbrain boundaries initially behave as a pool of non-neurogenic progenitors expressing her9 in a Notch-independent manner.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Its expression is enriched in boundary cells compared to rhombomere compartments at early stages, and it remains mainly in proliferating radial glial cells of lateral domains all along the AP axis at later stages. Our results support the developmental strategy othat different Hes/Her genes maintain distinct neural progenitor populations (Chapouton et al , 2006; Stigloher et al , 2008; Sigloch et al , 2023) establishing the neurogenic asynchrony in neural tissues. Hindbrain boundaries initially behave as a pool of non-neurogenic progenitors expressing her9 in a Notch-independent manner.…”
Section: Discussionsupporting
confidence: 76%
“…Our results support the developmental strategy othat different Hes/Her genes maintain distinct neural progenitor populations (Chapouton et al, 2006;Stigloher et al, 2008;Sigloch et al, 2023) establishing the neurogenic asynchrony in neural tissues. Hindbrain boundaries initially behave as a pool of non-neurogenic progenitors expressing her9 in a Notchindependent manner.…”
Section: Discussionsupporting
confidence: 75%
“…Among the transcriptional clusters, we identified leukocytes, differentiated stromal cells, and nine IEC types that included a cycling population enriched for the Notch mediator her15.1 (Figure 2B), a pan-stem cell marker in zebrafish [35][36][37] . Fluorescence in situ hybridization showed that her15.1+ cells are proliferative residents of the interfold base (Figure 2C), as expected for intestinal stem cells.…”
Section: Cellsmentioning
confidence: 99%
“…6C -D'', white arrowheads). Thus, Olig2 is negatively regulating the expression of her2 in the hypothalamus/posterior tuberculum, which is positively regulated by Notch signaling (Cheng et al, 2015;Sigloch et al, 2023). To determine whether Shh signaling is involved in regulation of olig2 expression in the posterior tuberculum/hypothalamus, we inhibited Shh signaling using Cyclopamine from 24 to 48 hpf (Fig.…”
Section: Olig2 Acts Upstream Of Her2 and Downstream Of Shh Signaling ...mentioning
confidence: 99%